GRIK3: A novel oncogenic protein related to tumor TNM stage, lymph node metastasis, and poor prognosis of GC - Baocheng Gong; Yuan Li; Zhenguo Cheng; Pengliang Wang; Lei Luo; Hanwei Huang; Shijie Duan; Funan Liu (Tumor Biology, 2017)
Glutamate receptor, ionotropic, kainate 3 (GRIK3), as a member of the glutamate kainate receptor family, mainly participated in neuroactive ligand receptor interaction pathway. Other members of GRIK family were previously reported to regulate cellular migration, transformation, and proliferation in tumor. However, the mechanism of GRIK3 in tumor is still unclear. Therefore, the purpose of our study was to reveal the expression and clinical significance of GRIK3 in gastric cancer (GC). First, we performed the expression analysis and survival analysis of GRIK3 using The Cancer Genome Atlas (TCGA) database, and the results showed that the GRIK3 expressed differentially between gastric cancer tissues and the adjacent normal tissues and that higher expression of GRIK3 was associated with poor survival outcomes. And the gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis suggested that GRIK3 mainly took part in cancer-related process. Subsequently, the validated immunohistochemistry showed that GRIK3 expressed higher in the GC tissues than in the matched normal tissues and the patients with overexpressed GRIK3 had worse survival outcomes. The univariate and multivariate analyses suggested that the expression of GRIK3 was an independent prognostic factor to predict GC prognosis. Furthermore, additional experiment showed that the lymph node metastasis tissues had higher GRIK3 expression than their matched primary GC tissues. These findings suggested that elevated GRIK3 expression could serve as an independent prognostic biomarker and a novel potential treatment target for patients with GC.